1982
DOI: 10.1111/j.1365-2125.1982.tb01936.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intrinsic sympathomimetic activity (ISA) during beta‐ adrenoceptor blockade in asthmatics.

Abstract: 1 Ten patients suffering from extrinsic bronchial asthma were examined. 2 In the pretreatment period, the histamine concentration required to produce a 20% decrease of forced expiratory volume in one second (FEVy) was 7.71 mg/ml. 3 Histamine provocation was repeated 2 h after administration of placebo, propranolol 40 mg, pindolol 5 mg or metoprolol 50 mg. After pindolol and metoprolol the histamine concentrations were slightly, but not significantly, lower than after placebo. After propranolol only 3.16 mg/ml … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
6

Year Published

1982
1982
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 2 publications
1
5
0
6
Order By: Relevance
“…However, Dorrow also showed that, when administered in equipotent doses, propranolol increased bronchial sensitivity to histamine while pindolol and metoprolol did not. 31 Other studies produced similar resultswhen pindolol was administeredintravenously. [32][33][34][35] However, Benson et al, in a study with five asthmatic patients, found that pindolol 5 mg po led to a significant reduction in the FEV compared with placebo."…”
Section: Pulmonary Functionsupporting
confidence: 53%
“…However, Dorrow also showed that, when administered in equipotent doses, propranolol increased bronchial sensitivity to histamine while pindolol and metoprolol did not. 31 Other studies produced similar resultswhen pindolol was administeredintravenously. [32][33][34][35] However, Benson et al, in a study with five asthmatic patients, found that pindolol 5 mg po led to a significant reduction in the FEV compared with placebo."…”
Section: Pulmonary Functionsupporting
confidence: 53%
“…We have previously reported a nega tive influence on different lung function parameters and on the bronchial reactivity of patients with symptom-free bronchial asthma [7], There is evidence that in these patients bronchoconstriction might not be solely induced by mere /3-adrenoceptor blockade [14]. The decrease in mucociliary clearance in coronary patients with a nor mal lung function observed in this study offers an additional factor for the bron chopulmonary risks of propranolol and other propranolol-like drugs.…”
Section: Discussionmentioning
confidence: 68%
“…Pindolol, which blocks //-and //¡-adrenoceptors, exhibits a neutral influ ence on lung function and mucociliary clearance due to its partial agonist activity [7]. Pharmacological studies suggest that the stimulant effects of pindolol are exert ed principally on //¡-adrenoceptors [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subject of partial agonist activity and lung function is discussed separately in the same issue of the journal (Louis, 1982;Dorow, 1982;Ruffin etal., 1982).…”
Section: Whithdrawal Symptomsmentioning
confidence: 99%